Intervenciones de enfermería prioritarias en el posoperatorio inmediato de histerectomía obstétrica de urgencia revisión - Negrete Analuisa, Nataly Silvana (2025)
Introduction: Nursing care of patients who have undergone emergency obstetric hysterectomy surgery, a procedure performed when conservative medical and surgical measures have failed to achieve hemostasis, during an obstetric complication, has significant maternal morbidity and mortality, making specialized nursing interventions essential. The objective was to systematize priority nursing interventions in the immediate postoperative period in patients undergoing emergency obstetric hysterectomy. Through a qualitative approach methodology, the scope was exploratory, descriptive, non - experimental, cross - sectional and developed from a literature review in recognized databases. The main result was the standardization of priority nursing interventions and the integration of a multidisciplinary approach in clinical practice, aimed at facilitating and guiding the work of staff in the immediate postoperative period and thus reducing the gap between current and appropriate care, optimizing the quality of care and mitigating the emotional impact. It was concluded that it is important to standardize priority nursing care in the immediate postoperative period with the intention of guiding the work, favoring decision - making and guaranteeing patient safety.